Differences in gestational age at preterm birth can predict future cardiovascular events in systemic lupus erythematosus (SLE) - Soh, May Ching; Nelson-Piercy, Catherine; Westgren, Magnus; McCowan, Lesley; Pasupathy, Dharmintra (Frontiers in Lupus, 2025)
IntroductionPregnancy complications from maternal placental syndrome (MPS) are associated with the accelerated development of cardiovascular events (CVE) in the parous cohort with systemic lupus erythematosus (SLE). Preterm birth may result from MPS, which is more common in SLE. This study aimed to determine if preterm birth stratified by gestational age increases the risk of CVE in SLE.MethodsUtilizing Swedish population databases between 1973 and 2011, those who had been pregnant with SLE were identified and stratified into three groups: term (≥37 + 0 weeks), late preterm 34 + 0–36 + 6 weeks, and early preterm <34 + 0weeks births. The primary outcome was CVE or death from CVE. The risk of CVE was calculated and adjusted for SLE-related morbidity and cardiovascular risk factors.ResultsOver the 38-year interval, there were 3,963 subjects, and the prevalence of preterm birth was 20.9%. The prevalence of CVE was 10.4% (n = 411), being highest in those who had given birth <34 + 0 weeks. After multivariable adjustment, the risk of CVE was 1.8 [adjusted hazards ratio (HR) 95% CI: 1.3–2.5] in those who birthed <34 + 0 weeks compared with others who had birthed at term. They also developed CVE earlier than those who birthed at later gestational ages.ConclusionsEarly preterm birth <34 + 0 weeks conferred a two-fold increased hazard for accelerated development of CVE. Reassuringly, those who delivered at a later gestation did not exhibit a similar risk of premature CVE. Therefore, birth <34 + 0 weeks, regardless of an underlying cause, may be a useful screening question to identify parous persons with SLE who are at greater risk of early CVE.